A low-power humidity sensor interface - Ye, Shu Qin. (2010)
Humidity sensors have a wide range of industrial applications including climate control, agriculture, food storage, domestic appliances and laboratory experiments. In this report, a brand new architecture of an SC amplifier interface circuit for humidity sensor application is developed. The sensing rationale behind is to use the difference between the thermal conductivity of air and water vapor at elevated temperatures. The difference in turn causes a voltage difference between two isolated sensing diodes. One of the diodes is sealed and has a fixed thermal conductance, while the other exposed to the environment having a humidity-dependent thermal conductance. The exposed diode is connected to the designed SC circuit, which can be easily monolithically integrated using a standard 0.18-µm process. Simulation results show that the humidity sensitivity of the sensor is 6.84, 12.44, 22.51mV/%RH for 20ºC, 30ºC and 40ºC respectively. One of the main advantages is that the circuit operates across the full range of humidity levels for environment temperatures from 20ºC to 40ºC. The amplifier operates under a supply voltage of 3V and dissipates power as low as 400µW.